ANALYSIS OF THE IMPACT OF IMPLEMENTING AKHLAK CORE VALUES BY STATE-OWNED ENTERPRISES (BUMN) ON EMPLOYEE PERFORMANCE AT PT PP SEMARANG-DEMAK - Hafidz Maulana; Muafi, Muafi (Publikasi Inspirasi Indonesia, 2025)
This study aims to analyze the impact of implementing the AKHLAK values by State-Owned Enterprises (BUMN) on employees of PT PP Semarang-Demak, particularly within the Toll Road Business Entity (BUJT) and Toll Road Regulatory Agency. Through a four-month internship program, the author was directly involved in human capital activities. The research methods employed include in-depth interviews, direct observation, and literature review. The results indicate that all informants understand and consider the AKHLAK values as important behavioral guidelines for employees. These values have been internalized into daily operational activities and have positively influenced employee performance. However, the evaluation process of the AKHLAK values implementation is not yet structured quantitatively due to the lack of specific measurement tools. This study recommends that PT PP Semarang-Demak develop a more structured and consistent evaluation system, as well as strengthen the internalization of the values through training and leadership example, so that the AKHLAK values can become a work culture that supports the company's long-term performance.